Differentiating Hemangioblastomas from Brain Metastases Using Diffusion-Weighted Imaging and Dynamic Susceptibility Contrast-Enhanced Perfusion-Weighted MR Imaging - She, D.; Yang, X.; Xing, Z.; Cao, D. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: On DWI and DSC-PWI, hemangioblastomas and brain metastases may exhibit different signal intensities depending on their cellularity and angiogenesis. The purpose of this study was to evaluate whether a hemangioblastoma can be differentiated from a single brain metastasis with DWI and DSC-PWI.MATERIALS AND METHODS: We retrospectively reviewed DWI, DSC-PWI, and conventional MR imaging of 21 patients with hemangioblastomas and 30 patients with a single brain metastasis. Variables of minimum ADC and relative ADC were acquired by DWI and the parameter of relative maximum CBV, by DSC-PWI. Minimum ADC, relative ADC, and relative maximum CBV values were compared between hemangioblastomas and brain metastases by using the nonparametric Mann-Whitney test. The sensitivity, specificity, positive and negative predictive values, accuracy, and the area under the receiver operating characteristic curve were determined.RESULTS: Both the minimum ADC values and relative ADC ratios were significantly higher in hemangioblastomas compared with brain metastases (P < .001 for both minimum ADC values and relative ADC ratios). The same was true for the relative maximum CBV ratio (P < .002). The threshold value of ≥6.59 for relative maximum CBV provided sensitivity, specificity, and accuracy of 95.24%, 53.33%, and 70.59%, respectively, for differentiating hemangioblastomas from brain metastases. Compared with relative maximum CBV, relative ADC had high sensitivity (95.24%), specificity (96.67%), and accuracy (96.08%) using the threshold value of ≥1.54. The optimal threshold value for minimum ADC was ≥1.1 × 10−3 mm2/s.CONCLUSIONS: DWI and DSC-PWI are helpful in the characterization and differentiation of hemangioblastomas from brain metastases. DWI appears to be the most efficient MR imaging technique for providing a distinct differentiation of the 2 tumor types.ADCminminimum ADCrADCrelative ADCrCBVrelative CBVrCBVmaxrelative maximum CBVROCreceiver operating characteristicAUCarea under the curve